Rivers - Jennings, Terry J. (Parsippany, NJ : Silver Burdett Press, 1998)
Describes the water cycle, erosion, environment, and ecosystems of rivers.
Includes index.
L.A. Recommended Foreign Language.
3.5
3-6
Keywords: Rivers -- Juvenile literature; Rivers; Rivers; Rivers